ANALISIS DAMPAK LALU LINTAS PEMBANGUNAN APARTEMEN HUNDRED RESIDENCE JL. RAYA GUBENG KOTA SURABAYA - Adiputro, Sapto; Santosa, Rudy (Universitas Dr. Soetomo, 2020)
The construction of Hundred Residence Apartment Jl. Raya Gubeng No. 102-106, Surabaya will provide an additional volume of traffic that burdens the streets around Jl. Raya Gubeng. Referring to these conditions, this final project research aims to explain about how the performance of the affected road for existing conditions, then due to the generation of Hundred Residence Apartments within the period of the plan and provide advice related to traffic management and engineering to minimize the occurrence of decreased service levels and performance intersections in the area around development. This thesis research uses quantitative and qualitative descriptive methods that refer to the 1997 Indonesian Road Capacity Manual (MKJI). From the results of the analysis it is concluded that the worst performance that ranks first is at the intersection of Jl. Pandegiling - Jl. Dinoyo - Jl. Keputran - Jl. Sulawesi. The existing conditions in 2019 have shown poor performance with the value of LOS E at peak hours in the afternoon and the average deviation delay value of 53.71 seconds / smp, then the analysis of conditions in the predicted year of 2026 shows a declining performance with LOS values F at the peak hour of the afternoon and the average intersection delay value of 178.92 seconds / junior high. This should be a concern so that later the existence of apartments does not add a negative impact on the performance of traffic around the development area. For this reason, traffic management and engineering needs to be done both inside and outside the apartment area to anticipate problems that are expected to emerge.